The Influence of Herbal Medicine on Platelet Function and Coagulation: A Narrative Review - McEwen, Bradley J. (Seminars in Thrombosis and Hemostasis, 2015)
Cardiovascular disease (CVD) is the leading cause of death worldwide. Platelet activation and aggregation play a central role in hemostasis and thrombosis. Herbal medicines have been traditionally used in the management of CVD and can play a role in modifying CVD progression, particularly in platelet function, and have the potential of altering platelet function tests, as well as some coagulation parameters. Herbal medicines, such as feverfew, garlic, ginger, ginseng, motherwort, St John's wort, and willow bark, were found to reduce platelet aggregation. In vitro studies show promise in the reduction of platelet aggregation for Andrographis, feverfew, garlic, ginger, Ginkgo, ginseng, hawthorn, horse chestnut, and turmeric. In addition, cranberry, danshen, dong quai, Ginkgo, ginseng, green tea, and St John's wort were found to have potential interactions with warfarin. Furthermore, St John's wort interacted with clopidogrel and danshen with aspirin. Therefore, repeat testing of platelet function and coagulation studies, particularly for patients on warfarin therapy, may be required after exclusion of herbal medicines that could have possibly affected initial test results.
Keywords: cardiovascular disease; platelet aggregation; platelet function; herbal medicine; warfarin